2011
DOI: 10.1039/c0lc00603c
|View full text |Cite
|
Sign up to set email alerts
|

A device for extraction, manipulation and stretching of DNA from single human chromosomes

Abstract: We describe the structure and operation of a micro/nanofluidic device in which individual metaphase chromosomes can be isolated and processed without being displaced during exchange of reagents. The change in chromosome morphology as a result of introducing protease into the device was observed by time-lapse imaging; pressure-driven flow was then used to shunt the chromosomal DNA package into a nanoslit. A long linear DNA strand (>1.3 Mbp) was seen to stretch out from the DNA package and along the length of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…21,35 Technical advances now allow one to isolate, confine, and manipulate single chromosomes in narrow channels. 37,38 The interrelationship between intrachain ordering and interchain organization described in this work will be useful for further exploiting the entropic mechanism …”
Section: Discussionmentioning
confidence: 99%
“…21,35 Technical advances now allow one to isolate, confine, and manipulate single chromosomes in narrow channels. 37,38 The interrelationship between intrachain ordering and interchain organization described in this work will be useful for further exploiting the entropic mechanism …”
Section: Discussionmentioning
confidence: 99%
“…Then 30 μL of 0.1 mg/mL Proteinase K in buffer [0.1 mg/mL BSA, 3% (vol/vol) 2-Mercaptoethanol, 0.5% Triton-X, and 0.5× degassed Tris-borate EDTA] was loaded into the inlet port; immediately after, 5 μL of stained cell extract containing 50-100 chromosomes was added. Protease digestion of the chromosomes was performed by heating the temperature of the solution inside the wells to 37-40°C with a heating cartridge at the center of the chuck in contact with the backside of the device (16). DR Mapping Acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…Microfluidic laboratory-on-a-chip devices have been used to separate individual chromosomes and extract genomic DNA (15,16), enabling haplotype-phased genotype and sequence to be obtained. Meanwhile, laboratory-on-a-chip systems incorporating nanofluidics have been used to stretch and map DNA (17)(18)(19), but their application to detecting SV has remained theoretical due to technical limitations of the designs used.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Rectangular nanochannels or approximations thereof are by far the most widespread experimental geometry, since these shapes are amenable to standard lithographic techniques. In an intriguing alternate approach, Huh et al 9 showed that mechanical deformation of cracked polydimethylsiloxane (PDMS) leads to isosceles triangular nanochannels, where the apex angle and the size of the nanochannels depend on the strain applied to the material.…”
Section: Introductionmentioning
confidence: 99%